2012
DOI: 10.4021/wjnu2w
|View full text |Cite
|
Sign up to set email alerts
|

Renal Resistive Index and Urinary N-acetyl-?-glucosaminidase as Predictors of Early Renal Involvement in Patients WithEssential Hypertension

Abstract: Background: The long-standing essential hypertension causes renal injury. N-acetyl-β-glucosaminidase (NAG) was considered as an indicator of the functional status of the renal tubules. The resistive index (RI), measured at the level of the interlobar arteries, is thought to reflect downstream vascular impedence and therefore, has been suggested as a measure of renal arterial stiffness. The aim of this study was to investigate whether changes in renal function assessed by urinary N-acetyl-β-glucosaminidase (NAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Mousa and co-workers demonstrated that the level of urinary NAG excretion was significantly increased in hypertensive patients compared with normotensive subjects. The upregulated urinary NAG excretion statistically correlated with patient age, serum uric acid, and duration of hypertension [17]. Zhang et al tracked the progression of nephropathy in hypertensive and obese SHROB rats versus control hypertensive SHR-lean rats.…”
Section: N-acetyl-beta-d-glucosaminidasementioning
confidence: 99%
“…Mousa and co-workers demonstrated that the level of urinary NAG excretion was significantly increased in hypertensive patients compared with normotensive subjects. The upregulated urinary NAG excretion statistically correlated with patient age, serum uric acid, and duration of hypertension [17]. Zhang et al tracked the progression of nephropathy in hypertensive and obese SHROB rats versus control hypertensive SHR-lean rats.…”
Section: N-acetyl-beta-d-glucosaminidasementioning
confidence: 99%